Animal protection in China and Japan: The ambiguous status of companion animals in rapidly changing societies - Doi, Kazushige; Pettier, Jean-Baptiste (Taylor and Francis, 2018)
CRIS-Team Scopus Importer:2023-03-21

A question of bank notes, cars, and houses! Matchmaking and the Moral Economy of Love in Urban China - Pettier, Jean-Baptiste (Comparative Studies in Society and History, 2022)
Chinese practices of matchmaking have been controversial for over a century. Their continued transformations reveal a complex nexus of sentimental and material dimensions in the marriage-decision process at the heart of the negotiations between families and in their selections of proper candidates. This interplay between personal sentiments, concrete considerations, and the desire for success makes marriage controversial, as love is claimed and proclaimed at the same time. Moral debates around materialism, which have reverberated through the public sphere over the last decade, show how love acts as a tool of social reproduction while it also expresses sincere aspirations for an emotionally satisfying life. In comparative perspective, the complex of romantic love examined here reveals a recent, original synthesis of the tradition of parental arrangement and the political question of the place of love in modernity. The paper elucidates one of the contradictions within Chinese society today: the family remains central, but wider trends of individualization continue to unfold. A multifaceted understanding of love clarifies how it can bind families together while it also discourages others from pursuing romance.
CRIS-Team Scopus Importer:2023-03-21
Keywords: cultural capital.; familism; individualization; marriage; matchmaking; materialism; morality; romantic love; sentiments

Marrying the perfect child — Middle class norms and intergenerational arrangements in the marriage corners of urban China - Pettier, Jean-Baptiste (Ethnography, 2020)
Caught in the context of a highly competitive development process, within the framework of a policy which limited their reproductive capacity to a single child, PRC urban families have, in recent decades, attached growing importance to their child's education, aiming to lead them to professional and personal success. This, however, also had an impact on the capacities of many young adults to marry early. In this context, the phenomenon of “marriage corners” mushroomed in large cities all over China beginning in the mid-2000s. Within China, this new practice generated criticism. These markets are seen as displaying conservative forms of marriage arrangement, the disregarding of romantic love, and forms of intergenerational power organization that may be considered backwards. However, by the criticisms it generates but as well the forms of relationships that it displays, the phenomenon can allow for a better understanding of the transformation of inter-generational relationships amongst urban middle-class, and on the norms framing the lives of the new generation.
CRIS-Team Scopus Importer:2023-03-21
Keywords: children; China; family; Marriage; norms; parents

Reinventing matchmakers: Ethnography of a matrimonial service agency in urban China La réinvention des marieuses Ethnographie d'une agence matrimoniale en Chine urbaine - Pettier, Jean-Baptiste (Homme, 2019)
Matchmakers are an ancient social institution in China. In order to control families and social mores, the imperial state had long imposed their use. Considered as an obstacle to the emancipation of the new generations at the turn of the twentieth century, and as such as a cause of China's lagging behind, they were forbidden by the Communist regime. However, the practice of matchmaking never completely disappeared at all, and the economic reforms implemented since the 1980s seem to have accelerated its reinvention. Whereas traditionally matchmakers were an indispensable part of any « respectable» wedding, today, however, they connote a lack of personal autonomy on the part of the wedding couple. Thus, the changed social position of the matchmakers transforms classical theoretical questions concerning the role of the individual and his/her personal sentiments in the choice of a spouse in China. his articles demonstrates how through the present ethnography of a marriage service agency in the city of Chengdu.
CRIS-Team Scopus Importer:2023-03-21
Keywords: China; Family; Individuals; Marriage; Matchmaker; Modernity; Sentiments

Saving China’s dogs: social transformation and moral conflicts in Chinese society - Pettier, Jean-Baptiste (Critical Asian Studies, 2021)
To be considered worthy of society’s protection is not the objective consequence of an inherent quality but the result of a social process. This article examines this observation through the case of canine welfare in China. Popular defense of dogs against brutalization and consumption, as well as state regulations, have become common in China in recent years, generating conflicts over the value attributed to dogs. To understand the circumstances behind and broader implications of activists’ support for protecting dogs, this article identifies elements that are determinant: framing; prioritization; the relationship between protectors and protected; and the socio-political background of these campaigns.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Animal rights campaigns; animal welfare; dog protection

The Paradoxical Agora The Social and the Political in between the People in the Marriage Corners of China - Pettier, Jean-Baptiste (Social Analysis, 2022)
Where is the political located? Since the early 2000s, the phe-nomenon of ‘marriage corners’ has mushroomed in city parks all over China. It consists of public gatherings attended by middle-to upper-middle-class parents attempting to find a partner for their child. The competitiveness of these gatherings and the vocabulary used by the participants when evaluating each other reflect political tensions of Chinese society without articulating them. Exploring this tension, the article argues for attending to the political ramifications of spaces where politics are silenced and denied. Hence, these marriage corners are examined as ‘paradoxical agoras’, that is, as constrained public spaces where politics are neither discussed nor decided, but rather embodied and practiced.
CRIS-Team Scopus Importer:2023-03-21
Keywords: China; market; marriage; ordinary politics; social competition